Combination of high-pressure treatment, mild heating and holding time effects as a means of improving the barrier properties of gelatin-based packaging films using response surface modeling. (August 2015) - Molinaro, Stefano; Cruz-Romero, Malco; Sensidoni, Alessandro; Morris, Michael; Lagazio, Corrado; Kerry, Joe P.
Abstract: The optimum combination of high-pressure (HP), mild temperature application and holding time on pigskin-derived, gelatin-based, film-forming solutions to improve the barrier properties of packaging films was determined using response surface methodology. Results showed that the variable response oxygen transmission rate (OTR) decreased significantly using a combination of temperature, time, and the interaction between pressure and time. The determined optimum conditions to minimize the OTR were high pressure treatment (600 MPa) and holding time (30 min), while maintaining the temperature at 20.5 °C. In parallel, films obtained at the optimum conditions (OPT) were characterized for structural, thermal, mechanical, water vapor transmission rate (WVTR) and color properties. OPT films were significantly affected by mechanical (TS), thermal ( T m ), WVTR properties and redness a* values compared to untreated control samples. Overall, a combination of HP, mild temperature and holding time on film-forming solutions showed interesting potential in altering film characteristics, especially in the enhancement of barrier properties. Industrial relevance: Results obtained in this study are of considerable importance for the film development and the shelf-life of food products packaged in films treated with the methodology used in the current work. The oxygen permeation through the film packaging can lead to a degradation of the quality attributes of the food products influencing microbial development as well chemical and enzymatic degradation pathways. Oxygen is responsible for oxidative rancidity of unsaturated fats with the development of undesirable flavors and aromas and a loss in vitamin C. The package oxygen permeability plays a key role in affecting the internal partial pressure of a packaging system and for this reason the oxygen permeability is probably the property mostly tested for the different packaging materials. Within this contest, the industrial relevance of this study is significant, since the results showed a potential application of a combination of high-pressure, mild treatment and holding time to increase barrier properties in bio-sourced packaging films thus extending the shelf-life of foodstuffs. Highlights: RSM was used to evaluate the combination of high-pressure, mild temperature and holding time on gelatine resulting films. OTR of films decreased significantly using a combination of temperature, time, and interaction between pressure and time. The optimum conditions to minimize the OTR were determined at the highest level of pressure applied and holding time. Mechanical, thermal and WVTR properties of films produced at the optimum conditions were significantly affected.